Agriculture in the Malaysian Region - Hill, R. D. 1935-, (Ronald David) (Singapore : NUS Press, 2013)
Covering Malaysia, Singapore and Brunei, Agriculture in the Malaysian Region, originally published in 1982, presents a detailed description of the region's agro-systems, including shifting cultivation, wet rice production, smallholder tree-crop and mixed forms cultivation, plantation systems, and intensive market-gardening with livestock production.
Includes bibliographical references and index.
Keywords: Agriculture -- Economic aspects -- Malaysia; Agriculture -- Malaysia -- History; Traditional farming -- Malaysia; Agriculture -- Economic aspects -- Singapore